Optimization of the Air-Conditioning Energy Performance and Daylight Performance of A Residential Building According to the Bioclimatic Design Principles: An Application to the Moroccan Mediterranean - Ameur, Mohamed; Kharbouch, Yassine; Taoukil, Driss; Mimet, Abdelaziz (International Journal of Sustainable Construction Engineering and Technology, 2024)
The bioclimatic architecture concept refers to an approach that takes into account the various characteristics of a building environment to make it more comfortable for its occupants. This work aims to improve the passive design parameters of an air-conditioned residential building located in the north of Morocco, in accordance with bioclimatic principles. The bioclimatic chart diagram is used to select the passive design measures that are the most appropriate for the north Morocco climate characteristics. Then, a set of design parameters are selected for more delimitation in the optimization study. The optimization problem is multi-objective and aims to find the design solution that simultaneously includes the best air-conditioning energy performance and daylight performance. The obtained results showed that the multi-objective optimum design solution is characterized by massive walls and roof, exterior insulation, double window glazing type, and a high summer ventilation rate. Also, a small glazing area with a large sun-shading covering is needed for the east facade. Ultimately, the building performance analysis revealed that the optimum bioclimatic design solution fully meets the requirements established by the Moroccan Building Thermal Regulation (MBTR), leading to an energy performance improvement of about 52%.